2016
DOI: 10.5152/tao.2016.1603
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cases who Underwent Reconstruction Through Pectoralis Major Myocutaneous Flap After Laryngopharyngectomy

Abstract: Objective: In this retrospective study, we discussed the results of patients who underwent hypopharynx reconstruction through a pectoralis major myocutaneous flap (PMMF) after laryngopharyngectomy. Methods:Twenty-three patients who underwent total laryngectomy, subtotal pharyngectomy, and/ or esophagus upper segment resection due to advanced-stage (T3 and T4) laryngeal, hypopharyngeal, and esophagus upper segment-located squamous cell carcinoma and subsequent reconstruction with PMMF were retrospectively evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…In total, 23 eligible studies for partial hypopharyngeal defects following TLE were selected for inclusion. The included studies reported data on complications and functional outcomes after PMMC flap (n = 13) [9,[11][12][13][14][15][16][17][18][19][20][21][22], pectoralis major myofascial flap (PMMF flap, n = 2) [5,9], RFFF (n = 5) [23][24][25][26] and ALTFF (n = 7) [22,[26][27][28][29][30][31][32] reconstructions. The numbers of patients included in each reconstructive group were the following: 394 (PMMC flap), 57 (PMMF flap), 160 (RFFF) and 183 (ALTFF), with a total of 794 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 23 eligible studies for partial hypopharyngeal defects following TLE were selected for inclusion. The included studies reported data on complications and functional outcomes after PMMC flap (n = 13) [9,[11][12][13][14][15][16][17][18][19][20][21][22], pectoralis major myofascial flap (PMMF flap, n = 2) [5,9], RFFF (n = 5) [23][24][25][26] and ALTFF (n = 7) [22,[26][27][28][29][30][31][32] reconstructions. The numbers of patients included in each reconstructive group were the following: 394 (PMMC flap), 57 (PMMF flap), 160 (RFFF) and 183 (ALTFF), with a total of 794 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Funnel plots of the primary outcome measures are shown in Figure A1 (online supplement), showing considerable asymmetry for studies reporting on fistula and stricture rates, indicating a high heterogeneity and the risk of publication bias. [5,9,11,12,[14][15][16][17][18][19][20][21][23][24][25][26]28,29,31,32].…”
Section: Resultsmentioning
confidence: 99%
“…After title/abstract screening, 111 articles were selected for full text assessment. Through the application of the defined inclusion and exclusion criteria, 13 studies were included in the qualitative and quantitative analysis (Balasubramanian et al, 2018; Ho et al, 2012; Hong et al, 2009; Kim & Kim, 2013; López et al, 2013; Ooi et al, 2017; Somuk et al, 2016; Song et al, 2011; Spriano et al, 2002; Spyropoulou et al, 2011; Su & Chiang, 1995; Tan et al, 2011; Yu et al, 2010). The reasons behind the exclusion of 98 studies are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Использование выращенного из кожи пациента эпителиального пласта вместо полнослойного аутодермолоскута позволяет избежать таких осложнений, как врастание волос в просвет гортани, стенозирование просвета верхних пищеварительных путей в послеоперационном периоде. Осложнения в виде свищей, наблюдаемые у пациентов в нашем исследовании, составляют 44%, что сопоставимо с известной из литературных данных частотой свищей у пациентов, получивших предоперационное облучение, которое колеблется от 13 до 50% [17]. У 56,5% пациентов после реконструктивных операций с использованием кожно-мышечных лоскутов описывают затруднение глотания твердой пищи, а у 21,7% -трудности при глотании как твердой, так и жидкой пищи [17].…”
Section: Discussionunclassified
“…Осложнения в виде свищей, наблюдаемые у пациентов в нашем исследовании, составляют 44%, что сопоставимо с известной из литературных данных частотой свищей у пациентов, получивших предоперационное облучение, которое колеблется от 13 до 50% [17]. У 56,5% пациентов после реконструктивных операций с использованием кожно-мышечных лоскутов описывают затруднение глотания твердой пищи, а у 21,7% -трудности при глотании как твердой, так и жидкой пищи [17]. В нашем исследовании у 1 (11%) больного был стеноз глотки, который после проведения бужирования стал причиной проблем с глотанием только твердой пищи.…”
Section: Discussionunclassified